Kemampuan Menganalisis Hubungan Simbol Dengan Makna Sila Kedua Pancasila Melalui Model Discovery Learning Pada Siswa Kelas V SD - Maria Marianti Bupu Teku; Maria Angelina Fransiska Mbari; Marianus Yufrinalis (Journal on Education, 2023)
This study aims to improve the ability to distinguish the meaning of the second precept of Pancasila through the Discovery Learning model using visual media (Microsoft office powerpoint, laptop, smartphone, projector/infocus) for fifth grade students at SDI Wairotang. This research is a classroom action research (CAR) designed to help teachers (researchers) find and solve learning problems that occur in class. This classroom action research will be carried out in cycles, between cycle I and cycle II. Samples taken as many as 10 people. The results showed that after giving action for two cycles the average value of the test results increased the ability to distinguish the meaning of the second precept of Pancasila using visual media in PKN subjects had increased. Cycle I The first meeting resulted in a score of 64% and the second meeting 69% with the category not fulfilling the KKM and in cycle II the score increased at the first meeting by 78% and at the second meeting by 94% which also increased by 100%. This shows that learning to increase the ability to distinguish the meaning of the second precept of Pancasila using visual media in PKN subjects can be further applied, in order to improve student achievement, especially in PKN subjects.